Digital Module of Scientific Writing Materials Based on TPACK for 11th Grade SMA/MA Students - Linda Nurmaya; Suherli Kusmana; Jaja Wilsa (International Journal of Educational Research Excellence (IJERE), 2024)
The purpose of this research is to design, validate, and implement digital modules for scientific writing based on TPACK (Technological Pedagogical and Content Knowledge) for 11th-grade SMA/MA students. The study uses the Research and Development (R&D) method and follows the ADDIE model, which includes analysis, design, development, implementation, and evaluation phases. The development process begins with an analysis of teacher needs, curriculum, and environmental factors. The TPACK-based scientific writing digital module is then validated by experts in material content, digital media, and practical application. The validation results indicate high feasibility, with assessments of 80%, 97%, and 78% from material, media, and practitioner experts, respectively. The structure of the module consists of three main sections: the beginning, content, and end. The beginning includes the cover, foreword, table of contents, glossary, and a draft map. The content section introduces the module’s identity, basic competencies, description, and usage instructions. Each learning activity contains objectives, material descriptions, summaries, practice questions, and self-assessment opportunities. Implementation results show a significant improvement in student learning outcomes. Before using the TPACK-based digital module, the average score was 69.86, which increased to 82.86-83.88 after its implementation. Statistical analysis using paired t-tests confirms the effectiveness of the module. The first t-test shows a value of 13.073 > 1.687 with a significance (2-tailed) of 0.000 < 0.005. The second t-test shows a value of 6.637 > 1.7109 with the same significance level. These results indicate a significant positive impact of the TPACK-based digital module on student learning outcomes. In conclusion, the study demonstrates that the TPACK-based scientific writing digital module is effective and significantly enhances students' learning achievements in scientific writing.